1991
DOI: 10.1038/bjc.1991.392
|View full text |Cite
|
Sign up to set email alerts
|

DNA aneuploidy and low S-phase fraction as favourable prognostic signs in metastatic melanoma

Abstract: (Clark et al., 1969) and thickness of tumour (Breslow, 1970) are known to predict the clinical behaviour of primary melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
3

Year Published

1993
1993
2004
2004

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 18 publications
2
9
3
Order By: Relevance
“…In our primary melanomas S-phase was higher in DNA aneuploid tumours as compared to DNA diploid ones, a result similar to previous findings (Hansson et al, 1982;Muhonen et al, 1991), after measurements on melanoma metastases.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…In our primary melanomas S-phase was higher in DNA aneuploid tumours as compared to DNA diploid ones, a result similar to previous findings (Hansson et al, 1982;Muhonen et al, 1991), after measurements on melanoma metastases.…”
Section: Discussionsupporting
confidence: 81%
“…patients with diploid tumours survived longer than those with aneuploid ones. This is also similar to findings with breast cancer (Stal et al, 1991) but in contrast to an earlier study which found that patients with aneuploid melanoma metastases had improved survival (Muhonen et al, 1991).…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…In our previous study on basically the same patient population we observed that DNA aneuploid melanoma patients showed a more favorable prognosis than did DNA diploid patients (8). Furthermore, this difference was more prominent among patients who had received systemic therapy, leading us to the conclusion that DNA aneuploid tumors might be more sensitive to chemotherapy than DNA diploid tumor.…”
Section: Discussionmentioning
confidence: 92%